A pluralistic approach to ecosystem services evaluation - Kerry Turner (University of East Anglia, The Centre for Social and Economic Research on the Global Environment (CSERGE), 2010)
The purpose of this note is to contribute to the emerging common understanding between the natural science, economic and social science perspectives on the 'value' of ecosystems and biodiversity. Given the inherent complexity of nature it is not surprising that the concept of 'value is capable of multiple interpretation and meaning. A number of different dimensions of nature-based value can be simply discerned and evaluated in different ways eg in monetary terms via economic analysis; in biophysical and geochemical terms via natural science; and in more qualitative terms via sociology, cultural geography, arts and humanities etc. Each of these value dimensions has validity in its own domain.
Keywords: 330; Ecosystem services; ecosystems; biodiversity; natural science; economic and social sciences; Biodiversität; Umweltqualität; Ethik; Werturteil; Pluralismus; Naturwissenschaft; Wirtschaftswissenschaft; Sozialwissenschaft